Phenotypic and genotypic aspects of Townes-Brock syndrome: case report of patient in southern Brazil with a new SALL1 hotspot region nonsense mutation - Paulo Breno Noronha Liberalesso; Mara L. Cordeiro; Simone Carreiro Vieira Karuta; Karyn Regina Jordão Koladicz; Anderson Nitsche; Bianca Simone Zeigelboim; Salmo Raskin; Michael Rauchman (BMC, 2017)
Abstract Background Townes-Brocks syndrome (TBS) is a rare autosomal dominant condition characterized by renal, anal, limb, and auditory abnormalities. TBS diagnosis can be challenging in settings where genetic analysis is not readily available. TBS traits overlap with those of Goldenhar and VACTERL syndromes. Case presentation Here, we present the case of a 5-year-old Brazilian boy born with an anorectal abnormality, limb and external ears malformations, genitourinary anomalies, and a congenital heart defect. Genetic analysis revealed a SALL1 nonsense mutation. The case is discussed in the context of the current literature. Conclusions Because of the variability in TBS clinical presentation, genetic analysis is key to the differential diagnosis of TBS relative to phenotypically similar syndromes.